Therapeutic inertia and intensified treatment in diabetes mellitus prescription patterns: A nationwide population-based study in Taiwan. (December 2016) - Huang, Li-Ying; Yeh, Hseng-Long; Yang, Ming-Chin; Shau, Wen-Yi; Su, Syi; Lai, Mei-Shu
Objective: To measure therapeutic inertia by characterizing prescription patterns using secondary data obtained from the nationwide diabetes mellitus pay-for-performance (DM-P4P) programme in Taiwan. Methods: Using reimbursement claims from Taiwan's National Health Insurance Research Database, a nationwide retrospective cohort study was undertaken of patients with diabetes mellitus who participated in the DM-P4P programme from 2006–2008. Glycosylated haemoglobin results were used to evaluate modifications in therapy in response to poor diabetes control. Prescription patterns were used to assign patients to either a therapeutic inertia group or an intensified treatment group. Therapeutic inertia was defined as the failure to act on a known problem. Results: The research sample comprised of 168 876 patients with diabetes mellitus who had undergone 899 135 tests. Of these, 37.4% (336 615 visits) of prescriptions were for a combination of two types of drug and 27.7% (248 788 visits) were for a combination of three types of drug. The proportion of patients in the intensified therapy group who were prescribed more than two types of drug was considerably higher than that in the therapeutic inertia group. Conclusion: In many cases in the therapeutic inertia group only a single type of hypoglycaemic drug was prescribed or the dosage remained unchanged.